Answer:
The correct answer is option C
a = 10√3, b = 5√3, c = 15 and d = 5
Step-by-step explanation:
Points to remember
The angles of a right angled triangle, 30°, 60° and 90° then sides are in the ratio, 1: √3 : 2
<u>To find the value of variables</u>
From the figure we can see 2 right angled triangle with angle 30, 60 and 90
we get, d= 5 then b = 5√3
b = 5√3 the c = 5√3 * √3 = 15
and a = 2 * 5√3 = 10√3
Therefore the correct answer is option C
a = 10√3, b = 5√3, c = 15 and d = 5
Answer:
Step-by-step explanation:
The first box should be 20.
The second box should be 40
The third box should be .2
The fourth box should be .6
Answer:
<h2>
![\huge \: b) \: 59 \: i {n}^{2}](https://tex.z-dn.net/?f=%20%5Chuge%20%5C%3A%20b%29%20%5C%3A%2059%20%5C%3A%20i%20%7Bn%7D%5E%7B2%7D%20)
</h2>
Step-by-step explanation:
<h3>to understand this</h3><h3>you need to know about</h3>
- area of triangles
- area of rectangle
- PEMDAS
<h3>tips and formulas:</h3>
- rectangle opposite sides are equal
- area of rectangle:l×w
- area of triangle:½×h×b
<h3>let's solve:</h3>
the area of the rectangle is
4×7 in²
28 in²
the area of above triangle is
½×6×7 in²
3×7 in²
21 in²
the area of left side triangle is
½×5×4 in²
2×5 in²
10 in²
therefore,
the area of the polygon is
28+21+10 in²
<h3>59 in²</h3>
Answer:
Step-by-step explanation:
y
=
−
2
3
x
+
2
Explanation:
Given that we have the slope and a point on the graph we can use the point slope formula to find the equation of the line.
Point-Slope Formula:
y
−
y
1
=
m
(
x
−
x
1
)
, where
m
is the slope of the line and
x
1
and
y
1
are x and y coordinates of a given point.
We can summarize the information already given:
m
=
−
2
3
x
1
=
6
y
1
=
−
2
Using this information, we can substitute these values onto the point-slope formula:
y
−
(
−
2
)
=
−
2
3
(
x
−
(
6
)
)
y
+
2
=
−
2
3
(
x
−
6
)
The equation above is the equation of the line in point-slope form. If we wanted to have the equation in
y
=
m
x
+
b
form then we simply solve the equation above for
y
y
+
2
=
−
2
3
x
+
12
3
y
+
2
−
2
=
−
2
3
x
+
12
3
−
2
y
=
−
2
3
x
+
12
3
−
2
(
3
3
)
y
=
−
2
3
x
+
12
3
−
6
3
y
=
−
2
3
x
+
6
3
y
=
−
2
3
x
+
2